2023
DOI: 10.1155/2023/6251492
|View full text |Cite|
|
Sign up to set email alerts
|

The Perspectives of Surrogates and Healthcare Providers Regarding SDM (Shared Decision-Making)

Abstract: The purpose of this paper is to explore the attitudes of surrogacy and medical service providers toward SDM and to identify the barriers and promoters of SDM in this population. To this end, we conducted a qualitative study of surrogacy and medical service providers in the First Affiliated Hospital of Soochow University using semistructured interviews. Thirty participants (11 agents, 12 ICU physicians, and 7 ICU nurses) were interviewed. The three stakeholders showed different attitudes toward SDM. They report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%